PKM Pemanfaatan Serabut Kelapa Dalam Peningkatan Ekonomi di Tengah Pandemi Covid 19 di Kelurahan Lopian Kecamatan Badiri Kabupaten Tapanuli Tengah - Hutagalung, Heriyawan; Nur Simamora, Fauziah; Safwan Koto, Mhd. (COVIT (Community Service of Tambusai), 2023)
The objectives of implementing this community partnership program (PKM) service are (1) understanding of PKM in the Lopian community, (2) understanding of the use of coconut fiber into flower pots, (3) understanding of the importance of developing village potential during the Covid-19 Pandemic and how to prevent the spread of Covid-19. The method of implementing coconut fiber utilization activities into flower pots includes four stages, namely: (1) Introduction Stage, (2) Socialization and Audience Stage, (3) Training and Processing Stage, (4). Final Evaluation Stage. The PKM community service partner is the Lopian Village, Badiri District, Central Tapanuli Regency. This program is one of the efforts to add insight to the community in the processing of coconut fiber. This activity is also useful as an innovation in making products, namely flower pots and improving the economy of local residents. Keywords: Covid 19, Utilization, Pot, Coconut Fiber